(untitled) (Research, Society and Development, 2021)
Access is the timely use of services in order to meet the needs of the user. As an alternative to the traditional model, the Advanced Access (AA) model appears in Canada , with schedules restricted to specific cases. Objectives: The purpose of this article is to analyze the existing scientific production about the Advanced Access model in Primary Health Care. Methods: Integrative literature review using the descriptors (1) “Health Care Accessibility” OR “Primary Health Care” AND and (2) "Advanced Access" in the PubMed, Scopus and BIREME databases. Selection criteria were studies published in the last five years, available in Portuguese, English or Spanish and dealing with the theme. Results: Eight studies were selected, six were grouped into two categories of analysis: “The Canadian experience with AA : a model in consolidation”; and “The Brazilian experience with AA: local experiments” and the other two contributed to enrich the discussion. The AA stands out to balance capacity and demand with physical infrastructure and adequate staff, both in the international arena, as the experiences of municipalities, improving the quality of APS. Conclusion: Studies that detail the AA in its practice, as well as the challenges and needs, can inspire other health units to study it and consider its implementation if it is appropriate for its context, aiming to improve the health and care of its population.